006 Myocardial infarction and viability assessment by 12 lead ECG vs gold standard cardiac magnetic resonance. (5th May 2016) - Dastidar, Amardeep Ghosh; Carpenter, Alexander; Rodrigues, Jonathan; Palazzuoli, Alberto; Wilson, Catherine; Kestenbaum, Samantha; Baritussio, Anna; Baumbach, Andreas; Nightingale, Angus; Bucciarelli-Ducci, Chiara
Abstract : Introduction: Q-waves on 12 lead ECG is considered a marker of transmural myocardial infarction (MI) and is used universally. Late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) accurately identifies MI and has become the gold standard for the assessment of myocardial viability. Aim: Determine the diagnostic accuracy of Q-waves to identify MI and predict regionality. Ascertain the CMR predictors of Q-wave. Methods: Data collected on 498 consecutive patients (mean age 64 years, 71% males) referred for CMR with suspected IHD. Patients with non-IHD were excluded. Q waves in ≥2 precordial leads from V1-V4 reflected LAD territory. Transmural infarction was defined as >50% LGE. Results: 290 patients demonstrated MI, 157 transmural and 133 sub-endocardial based on LGE. Diagnostic accuracy of Q-wave as a marker of transmural MI was 66% and as a predictor of previous MI was 55%. 126 had pathological Q-waves, 40% in LAD territory, 55% non-LAD and 5% a combination. Of those with anterior (LAD) Q waves, 68% demonstrated LAD territory LGE and in non-LAD Q waves, 67% demonstrated a non-LAD territory infarct by LGE. On multivariate analysis, total scar score and >75% thickness LGE were significant predictors of Q wave. Conclusion: Presence of pathological ECG Q-waves is not only a poor marker of myocardial scarring, but also a poor predictor of viability and regionality when compared to CMR. Presence of Q wave correlates only with total scar score and >75% LGE. In clinical decision-making, clinicians need to be aware of the limitations of ECG Q-waves.